2007
DOI: 10.1021/jp076346e
|View full text |Cite
|
Sign up to set email alerts
|

Dielectrophoretic Trapping of Single Bacteria at Carbon Nanofiber Nanoelectrode Arrays

Abstract: We present an ac dielectrophoretic (DEP) technique for single-cell trapping using embedded carbon nanofiber (CNF) nanoelectrode arrays (NEAs). NEAs fabricated by inlaying vertically aligned carbon nanofibers in SiO2 matrix are applied as "points-and-lid" DEP devices in aqueous solution. The miniaturization of the electrode size provides a highly focused electrical field with the gradient enhanced by orders of magnitude. This generates extremely large positive DEP forces near the electrode surface and traps sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
49
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 23 publications
6
49
0
Order By: Relevance
“…The generation of such patterns requires a relatively high concentration of polarizable particles and so is seen only when the particle flux is sufficiently high. Even though similar "pearlchain-like" patterns were observed by Suehiro et al in DEP trapping of E. coli cells between interdigitated microelectrodes [21], our previous DEP studies showed that only isolated E. coli cells were captured at the NE sites [15,16]. The larger size and higher internal conductivity of bacteria may have screened the high electric field at the NE tip and reduced the electrical interaction with additional cells.…”
Section: Resultssupporting
confidence: 72%
See 4 more Smart Citations
“…The generation of such patterns requires a relatively high concentration of polarizable particles and so is seen only when the particle flux is sufficiently high. Even though similar "pearlchain-like" patterns were observed by Suehiro et al in DEP trapping of E. coli cells between interdigitated microelectrodes [21], our previous DEP studies showed that only isolated E. coli cells were captured at the NE sites [15,16]. The larger size and higher internal conductivity of bacteria may have screened the high electric field at the NE tip and reduced the electrical interaction with additional cells.…”
Section: Resultssupporting
confidence: 72%
“…Comparing the above virus capture results to the previous reports on the DEP capture of E. coli cells with similar NEA devices [15,16], four novel observations were made: (1) the optimum AC frequency was found to be ~10 kHz for virus as compared to 100 kHz to 1 MHz for E. coli. (2) The DEP capture of virus particles was observed even at ~8.9×10 4 pfu·ml −1 , more than 4 orders of magnitude lower than the concentration (~1×10 9 cfu·ml −1 ) used in previous E. coli studies.…”
Section: Resultssupporting
confidence: 54%
See 3 more Smart Citations